Silicon nitride laser cladding: A feasible technique to improve the biological response of zirconia. (June 2020) - Marin, Elia; Zanocco, Matteo; Boschetto, Francesco; Santini, Michele; Zhu, Wenliang; Adachi, Tetsuya; Ohgitani, Eriko; McEntire, Bryan J.; Bal, B. Sonny; Pezzotti, Giuseppe
Abstract: Zirconia is the most common ceramic used in dental implants. Even if it possesses both mechanical strength and esthetics, its intrinsic bio-inertness often results in a lack of biological integration. On the other hand, Si3 N4 has been proved to be bio-active and to be able to easily osteointegrate. In this work, a Si3 N4 powder-based laser-cladding process has been developed in order to improve the biological response to biomedical zirconia. The process resulted in the formation of a composite coating with Si3 N4 particles dispersed in nano-crystalline/amorphous silicon. Microscopic observation showed that the layer is adherent to the substrate. The application of the laser cladding treatment resulted in an increase of the roughness, further enhancing the probability of interaction with biological tissues and consequently the bioactivity. Testing with human osteosarcoma cell lines resulted in the formation of bone tissue with high collagen maturity, high carbonate to phosphate ratios and good tissue mineralization, but lower cell proliferation when compared to stoichiometric Si3 N4 . The bone tissue quality parameters, as measured by Raman spectroscopy, resulted to be comparable to healthy human bone tissue and suggest that laser-cladded Si3 N4 treatments might be able to improve the stability of zirconia implants. Graphical abstract: Unlabelled Image Highlights: For the first time, laser cladding of Si3 N4 was used on ZrO2 substrates. The cladding was formed by a mix of Si3 N4 and amorphous/nano-crystalline Silicon. The cladded layer greatly improved the amount of bone tissue produced by SAOS-2. The Si3 N4 cladding can improve the osteointegrative properties of zirconia. This deposition process is flexible and can be adapted to most implant designs.